2019
DOI: 10.1136/bmjopen-2018-027673
|View full text |Cite
|
Sign up to set email alerts
|

Does weight-related stigmatisation and discrimination depend on educational attainment and level of income? A systematic review

Abstract: ObjectivesObesity is considered a global health issue, because of its health-related consequences and also because of its impact on social status as a result of stigma. This study aims to review the quantitative state of research regarding socioeconomic characteristics’ influence on weight-related stigmatisation and discrimination. Based on Bourdieu’s Theory of Class and his concept of ‘habitus’, it is assumed that people with a higher level of education and income show stronger negative attitudes towards peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 57 publications
(198 reference statements)
3
12
0
Order By: Relevance
“…Specifically, people with incomes greater than 2.5 times the minimum wage and people who had completed higher education presented more weight bias. These results are consistent with other studies and especially with a systematic review that indicated that weight discrimination attitudes increase with higher education and higher income 56 …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Specifically, people with incomes greater than 2.5 times the minimum wage and people who had completed higher education presented more weight bias. These results are consistent with other studies and especially with a systematic review that indicated that weight discrimination attitudes increase with higher education and higher income 56 …”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with other studies and especially with a systematic review that indicated that weight discrimination attitudes increase with higher education and higher income. 56 Overall, the evidence indicates that the people who are most likely to present weight discrimination are normal weight men, with an income greater than 2.5 times the minimum wage and well quali- guidelines, 57 given the sample size and that the results were in concordance with previous studies, we expect our findings to be generalized to other populations with similar sociodemographic characteristics (including all BMI ranges) and cultural characteristics. Also given the sample size and that the sample came from the general population, we predict this validation can be used to assess anti-fat attitudes in other Spanish language countries.…”
Section: Discussionsupporting
confidence: 80%
“…In some cultures, in which individual responsibility is described as the leading cause of self-fulfillment, health, and wealth, obesity can be seen as a self-inflicted condition. In other cultures, in which individuals' situations are considered a result of various circumstances, obesity might not be seen as self-inflicted [49]. In these cultures, especially people with a high level of education may be aware of social barriers as determinants for self-fulfillment, wealth, and health, including bodyweight (35).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the relationship between weight stigma and income or educational attainment is understudied, and available research does not provide consistent evidence. 31 American women may feel less financially satisfied than men with their medical care, perhaps due to lower income. 32 While research has tended to focus on how being at a lower income may precede weight gain, importantly, through discriminatory processes, being at a higher weight may affect income (particularly for women) in the United States.…”
Section: Weight Stigmamentioning
confidence: 99%